Design, synthesis, characterization, antimicrobial activity, cytotoxicity, molecular docking, and in-silico ADMET analysis of the novel cefuroxime derivatives - Ananta Kumar Das; Prosenjit Paul; Mahian Parveg Pranto; Md. Jahid Hassan; Koushik Saha; Md. Emdad Hossain (Elsevier, 2024)
This research aims to design and synthesize novel derivatives of Cefuroxime to evaluate their antibacterial effectiveness in comparison to Cefuroxime and to decrease resistance.Schotten Baumann's reaction synthesizes anhydride from acyl chlorides and carboxylate anion. Cefuroxime sodium was reacted with benzoyl chloride, 4-bromobenzoyl chloride, and 4-nitrobenzoyl chloride to make benzoyl derivatives. The derivatives were characterized using spectral analysis. Antimicrobial activity, cytotoxicity, in-silico molecular docking with nine different class of (Penicillin Binding Proteins) PBPs, and ADMET analysis were assessed for the analogs.Three molecules, Cef-1, Cef-2, and Cef-3, are synthesized from benzoyl derivatives. In various organisms, the derivatives outperformed Cefuroxime in antimicrobial activity. In many organisms, Cef-1 has the highest zone of inhibition. Cef-1 and Cef-3 inhibit Klebsiella pneumoniae better than Cef-2 and Cefuroxime. The greatest Cef-2-induced inhibition zone in Salmonella Typhimurium was 29.33 ± 0.47 mm. Significant antimicrobial susceptibility test activity was observed with lower inhibitory concentration (12.5 μg/ml) of derivatives compared to Cefuroxime across many species. Compound cytotoxicity is low, according to research. The consensus docking scores show that all synthesized derivatives bind better than cefuroxime. According to the results of the study, Cef-3 has the strongest correlation with PBP1a, PBP2a, PBP3, PBP4, and PBP6, whereas Cef-2 has a stronger association with PBP1b, PBP2b, PBP2x, and PBP5. Like Cef-2, Cef-1 has a greater affinity for PBP2x. Docking research indicated that all drugs bound better than Cefuroxime, indicating superior antibacterial efficacy. The ADMET studies showed oral bioavailability increased by increasing lipophilicity score 0.17 and cefuroxime 0.11.